Towards internal corporate venturing in a mature manufacturing firm : Case: MacGregor - Kolehmainen, Meri (My University, 2018)
One gained competitive advantage is not everlasting without continuous innovation. Consequently, the origins of this master’s thesis lay on the case company’s need to look for innovative solutions to gain and sustain corporate competitiveness and to ensure survival in current and future markets. All in all, internal corporate venturing (ICV) has been recognized as a viable tool for achieving corporate competitiveness. This thesis’ perspective in ICV research area is pragmatic. It utilizes the earlier research to study ICV as a way to structure the case company’s new business creation. This thesis aims to study how new business creation is currently arranged at the case company, what issues they should consider if starting ICV and finally how the case company could benefit from ICV. The research is conducted by qualitative single case study, utilizing an exploratory approach. The analysis is based mainly on interview data but complemented by field notes and quantitative data from employee survey conducted annually within the case company. Based on earlier research, a three-part framework was formed to study the enablers of successful ICV. This framework was utilized to study what issues the case company should if starting ICV. The research found four themes describing the challenges of the case company in new business creation. Those were decreased ability to act on new ideas, lack of organizational support, internal communication and external challenges. As a result of this study, it is suggested that effectual internal communication could be inserted to the framework of enablers of ICV, since ineffective internal communication was recognized causing challenges in new business creation within the case company. However, this subject needs a further research. Additionally, this thesis provided a four-part framework describing the issues the case company needs to address if starting ICV. This framework consists of shaping venturing-like environment, forming venturing team and venturing unit and tackling the other internal challenges which came up during this research within the case company. Finally, this thesis found that the main befit from ICV for the case company could be increased ability to act on new ideas.
Keywords: Internal corporate venturing, new business creation